Equinix Addresses Green Talent Gap in Singapore with S$160,000 Pledge towards Sustainability Scholarships at NUS and SMU - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
Since the launch of the Singapore Green Plan, the nation’s journey to becoming a low-carbon economy is moving forward with a deepening of workforce capabilities. According to LinkedIn, Asia-Pacific has seen 30% growth in hiring for green jobs — defined as jobs that cannot be done without sustainability skills — between 2016 and 2021.[1] Aiming to reduce the talent skills gap as sustainability becomes entrenched into regulation and public awareness, Equinix, Inc. (Nasdaq: EQIX), the world's digital infrastructure company™, today announced that it has pledged S$160,000 towards sustainability focused scholarships for programs administered by the National University of Singapore (NUS) and Singapore Management University (SMU).